2015
DOI: 10.4049/jimmunol.1501050
|View full text |Cite
|
Sign up to set email alerts
|

T Cell Adolescence: Maturation Events Beyond Positive Selection

Abstract: Single positive (SP) thymocytes that successfully complete positive and negative selection must still undergo one final step, generally termed T cell maturation, before they gain functional competency and enter the long-lived T cell pool. Maturation initiates after positive selection in SP thymocytes, and continues in the periphery in recent thymic emigrants (RTEs), before these newly produced T cells gain functional competency and are ready to participate in the immune response as peripheral naïve T cells. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
92
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(98 citation statements)
references
References 59 publications
(60 reference statements)
1
92
1
4
Order By: Relevance
“…Day 18 Pmel-iPSC-derived cells from OP9/DLL1 co-culture were stimulated with irradiated splenocytes in the presence of cognate hgp100 peptide for 8 days. As with naive CD8 + T cells, Pmel-iPSC-derived T cells expanded specifically in response to cognate peptide and released tumor necrosis factor (TNF) after re-stimulation with anti-CD3/CD28 (Figures S2G and S2H), indicating that they were proliferation-competent and functional, which are markers of T cell maturity (Hogquist et al, 2015). However, most cells lost surface expression of CD8β and obtained a CD8αα + or DN phenotype during expansion (Figure 1E), similar to when immature self-reactive T cells bind strongly to self-antigens (Yamagata et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Day 18 Pmel-iPSC-derived cells from OP9/DLL1 co-culture were stimulated with irradiated splenocytes in the presence of cognate hgp100 peptide for 8 days. As with naive CD8 + T cells, Pmel-iPSC-derived T cells expanded specifically in response to cognate peptide and released tumor necrosis factor (TNF) after re-stimulation with anti-CD3/CD28 (Figures S2G and S2H), indicating that they were proliferation-competent and functional, which are markers of T cell maturity (Hogquist et al, 2015). However, most cells lost surface expression of CD8β and obtained a CD8αα + or DN phenotype during expansion (Figure 1E), similar to when immature self-reactive T cells bind strongly to self-antigens (Yamagata et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…An investigation of genes within these pathways revealed that extrathymic T cells had decreased expression of classical MHC class I ( H2-D1 and H2-K1 ) and non-classical MHC genes ( H2-Q4 , H2-T3 , H2-T10 , H2-Q7 , H2-Ob , H2-DMb1 , and H2-DMa ) as well as increased expression of NK receptors ( Klrc1 , Klrc2 , and Klrc3 ) (Figure 1H). The down-regulation of MHC class I genes as well the upregulation of Ptcra , Rag1 , Rag2 , and Rorc suggest that extrathymic T cells have an immature T cell phenotype similar to immature CD8SP (CD8iSP) T cells, potentially because of an inadequate positive selection, impaired TCR signaling, or an unfinished allelic exclusion program (Figure 1I; Carpenter and Bosselut, 2010; Hogquist et al, 2015; von Boehmer, 2005). However, NK receptor expression also confirms potential innate-like features among the extrathymic T cells.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations